Morphological structure and functional group of Toraja robusta and arabica spent coffee grounds for electronic device applications - Dwi Prasetyawati Thana; Ishak Pawarangan; Wilson Jefriyanto; Martina Pineng; Eko Suripto Pasinggi; Rali Sarira Bone; Yosep Mari'; Conny Conny (Universitas Ahmad Dahlan, 2023)
Spent coffee grounds (SCG) are waste byproducts of the coffee brewing process and are frequently disposed of in landfills, which raises environmental issues. A thorough overview of the properties of coffee grounds has yet to accompany the utilization of coffee grounds in many applications. This study attempts to categorize different coffee grounds based on their morphological structure and composition/element characteristics using scanning electron microscopy (SEM) for microstructural analysis and Fourier transform infrared spectroscopy (FTIR) to figure out the functional groups in coffee grounds. Morphological structure analysis showed that Robusta and Arabica SCG were dominated by around 70% of carbon, oxygen, and nitrogen. FTIR analysis revealed seven different peaks in Robusta and Arabica coffee grounds. Finally, the high concentration of carbon in Robusta and Arabica coffee grounds led to promising electrochemical energy storage for electronics applications.